Peran Sekolah Dalam Membangun Karakter Toleransi Pada Siswa Multikultural - Athifa, Elcha; Fahira, Dwi Jihan; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Education has an important role in shaping the character of students, especially in the context of a multicultural society. Schools as formal institutions not only function to transfer knowledge, but also become a strategic space in instilling social values such as tolerance. This study aims to describe the role of schools in building tolerance character in students who come from different cultural, religious and ethnic backgrounds. The method used is a descriptive qualitative study with a literature study approach and field observations in several multicultural schools. The results showed that schools play an active role through integrating tolerance values in the curriculum, habituation of mutual respect in relationships, and organizing inclusive extracurricular activities. In addition, teachers and principals have a role as role models who reinforce these values in daily practice. However, there are still challenges such as the lack of teacher training in diversity management and social biases that sometimes arise in the school environment. Therefore, a more systematic and collaborative approach is needed between schools, families and communities in building a sustainable culture of tolerance.